Phthalate exposure aggravates periodontitis by activating NFκB pathway - Wei Wu; Wenxiu Jiang; Yongmiao Zhou; Zhewei Zhang; Guoqing Li; Chunbo Tang (Ecotoxicology and Environmental Safety, 2024)
Background: Phthalates are widely used plasticizers, which were identified as risk factors in the development of many human diseases. However, the effects of phthalates in the periodontitis are unknown. We aimed to investigated the relationship of periodontitis and phthalate exposure as well as the underlying mechanisms. Materials and methods: Univariate and multivariate logistic regressions were employed to evaluate the association between phthalate metabolites and periodontitis. The generalized additive model and piecewise logistic regression were conducted to investigate the dose-response relationship. Cell and animal models were used to explore the role and mechanism of DEHP in the development of periodontitis. Transcriptome sequencing, bioinformatics analysis, western blot, immunofluorescence and mice model of periodontitis were also employed. Results: MEHP (OR 1.14, 95% CI 1.05–1.24), MCPP (OR 1.08, 95% CI 1.00–1.17), MEHHP (OR 1.18, 95% CI 1.08–1.29), MEOHP (OR 1.18, 95% CI 1.07–1.29), MiBP (OR 1.15, 95% CI 1.04–1.28), and MECPP (OR 1.20, 95% CI 1.09–1.32) were independent risk factors. And MEHHP, the metabolite of DEHP, showed the relative most important effects on periodontitis with the highest weight (0.34) among all risk factors assessed. And the increase of inflammation and the activation of NFκB pathway in the periodontitis model mice and cells were observed. Conclusion: Exposure to multiple phthalates was positively associated with periodontitis in US adults between 30 and 80 years old. And DEHP aggravated inflammation in periodontitis by activating NFκB pathway.